Agroecological impacts of crop residue burning: a qualitative systematic review of direct and inferred evidence - Parambil-Peedika, Ashiq; Laing, Alison M.; Gathala, Mahesh Kumar; Adeeth AG Cariappa; Krishna, Vijesh V. (Elsevier, 2025)
The widespread adoption of mechanized crop harvesting in cereal-based production systems and limited turnaround time between cropping seasons have made crop residue burning a prevalent time-saving practice. Despite its well-documented environmental and health consequences, how residue burning affects agrobiodiversity and ecosystem functions remains underexplored. This qualitative systematic review includes a total of 250 peer-reviewed studies, of which 41 examined the direct effects of residue burning, and 209 focused on broader air pollution impacts as inferential evidence, of which 134 publications focused on arthropods and 75 on birds. From the 233 recorded trait instances across the studied species, about 40 % showed a negative response to residue burning, indicating improved biodiversity responses to alternative residue management practices, such as retention, incorporation, and manual or mechanical removal. Residue burning negatively affected natural predators but favored parasitic nematodes and rodent pests. More studies are required to better characterize the functional responses of important species across various agroecosystems. The decline in soil biodiversity and beneficial species due to residue burning significantly diminishes the ecosystem services these biodiversity components provide, ultimately threatening long-term system productivity. Arthropods and birds, which play critical ecological roles in agroecosystems, may also be adversely affected by residue burning. However, very few air pollution studies have explicitly examined the impact of residue burning on higher taxa. Findings from broader air pollution studies, used here as secondary evidence, offer valuable inferential insights into the potential ecological impacts of crop residue burning on birds and arthropods, mediated through changes in air quality. Despite these documented consequences, agrobiodiversity considerations are largely absent from policy discussions on residue management. Our findings highlight the urgent need for a comprehensive assessment of the ecological impacts of crop residue burning on biodiversity and associated ecosystem services to inform biodiversity conservation and climate mitigation efforts to ensure sustainability of agricultural systems.